COMPARISON OF READING METHODS OF ASBAB AN-NUZUL M. FAZLUR RAHMAN AND MOHAMMAD TOLBI - Ridho, Muhammad Izul; Ruslan, Muhammad (Pascasarjana UIN Kiai Haji Achmad Siddiq Jember, 2024)
Since the beginning of the emergence of studies on asbab al-nuzul, Muslim scholars have had different opinions about it. Some consider it the most important part of the process of understanding the holy text of the Qur'an, while others have the opposite opinion. But today almost all Muslim scholars consider the study of asbab al-nuzul to be the most important part of the process of understanding the meaning of the holy text. Even the scope of its understanding has been expanded, one of the Muslim scholars who took part in expanding the study of asbab al-nuzul is Fazlur Rahman and Muhammad Tolbi. Fazlur divided the category of asbab al-nuzul into two categories; Micro and Macro. Next, he developed his understanding of asbab al-nuzul into his double movement theory which finally anchored on the understanding of the universal and flexible meaning of the Qur'an. Not much different from Fazlur, Tolbi tried to explain the meaning of the Qur'an using an interpretation method based on understanding the text through the historical context of the text. Tolbi believes that the verses of the Qur'an should be interpreted in the context in which they were revealed. Removing the verses of the Qur'an from their historical aspects will only make the verses understood in an understanding that benefits certain parties. Although they appear the same, the methods of these two scholars are actually very different